Sustainability management strategies and impact in developing countries - Din, Mohd Fadhil Md; Alias, Nor Eliza; Hussein, Norelyza; Zaidi, Nur Syamimi (Community, environment and disaster risk management ;, 2022)
There has been increasing concern over the impacts of 21st century challenges, be it on environmental, social, and economic aspect. Rapid development, a global health pandemic and climate change are just some of the monumental challenges affecting us. While the foundation of knowledge surrounding these impacts is continuously expanding, the adaption of sustainability concepts is not yet established especially in developing countries. Sustainability Management Strategies and Impact in Developing Countries emphasizes on the research of sustainability management and strategies in developing countries. Covering topics on sustainability management in construction, education and in social behaviour, this 26th volume of the Community, Environment and Disaster Risk Management presents the importance of sustainability concepts as a vital element in development. Reviewing sustainable construction management including green schemes, industrial safety, adaptable frameworks, and policies from countries such as Malaysia, Vietnam and Nigeria, Sustainability Management Strategies and Impact in Developing Countries provides information to the public, researchers, planners, and stakeholders dealing with sustainability management and strategies, particularly for developing and emerging economic countries.